Excretion of Calcium, Phosphorus, Magnesium and Sodium in Lactating Sows - Novotný J.; Reichel P.; Kósa B.; Šipoš D. (Folia Veterinaria, 2016)
The aim of this study was to evaluate the excretion of calcium (Ca), phosphorus (P), magnesium (Mg) and sodium (Na) via milk, urine and faeces during the lactation period of sows. Six clinically healthy lactating sows (crossbreed Large White × Landrace) were selected for these experiments and were housed in standard conditions and fed with commercially prepared dry mixture for this category of sows. The blood serum, milk, urine and faecal samples were collected on the 7th, 14th, 21st, and 28th day of lactation. During four weeks of lactation, we recorded the relatively stable and physiological concentrations of Ca, P, Mg and Na in blood serum. The analysis of the sow’s milk showed the highest concentration of Ca and P at the end of lactation, while the highest concentration of Mg and Na was observed on the 7th lactation day. The following macro-mineral excretion was recorded in urine: 98.83-194.00 mg.l-1 for Ca; 11.88- 53.09 mg.l-1 for P; 171.67-344.05 mg.l-1 for Mg; and 56.50-74.83 mg.l-1 for Na; and in the faeces, 1824.5- 3045.5 mg.kg-1 for Ca; 1566.93-2483.2 mg.kg-1 for P; 1916.2-2505.2 mg.kg-1 for Mg; and 516.8-748.2 mg. kg-1 for Na.